Precolonial Black Africa a comparative study of the political and social systems of Europe and Black Africa, from antiquity to the formation of modern states - Diop, Cheikh Anta. (Westport, Conn L. Hill, 1987)
This comparison of the political and social systems of Europe and black Africa from antiquity to the formation of modern states demonstrates the black contribution to the development of Western civilization.
Translation of: L?Afrique noire pré-coloniale.
Keywords: Social structure --Africa, Sub-Saharan --History.